Representasi Aturan Adat Dalam Pengelolaan Hutan Masyarakat Adat Ammatoa Sulawesi Selatan - Syarif, Erman (Jurnal Environmental Science, 2018)
Pasang is the customary rule of the Ammatoa community in forest management. The objectives of this study are: 1) to identify the role of forests (boronga) for the Ammatoa indigenous people, (2) to identify customary rules in the management of Ammatoa indigenous peoples' forests. This type of research is qualitative using a phenomenology approach. The data sources in this study were Ammatoa (adat chief), Galla Puto (adat leader), Galla Pantama (adat leader), Ammatoa indigenous people, and cultural figures. Data collection is done by observation, interviews, Focus Group Discussion and documentation. Data verification strategy with data triangulation, member checks, and audit trail. The results of the study show that the Ammato’s people in managing forest resources are inseparable from their belief in tide teachings. Forest management is strengthened by the existence of Kasipalli (prohibitions) that should not be carried out in the forest area, namely Ta’bang Kaju (logging), Rao Doang (taking shrimp), Tatta ’Uhe (taking rattan), and Tunu Bani (burning bees). Each of these violations is always accompanied by customary sanctions. Customary sanctions given to forest destroyers who have been identified and captured by the community are divided into 3 parts, namely: Poko babbalak (pangkal cambuk), tangnga babbalak (middle whip), and cappa babbalak (tip of the whip). As for the unknown perpetrators, the Ammatoa performed Attunu Panroli (burning crowbar) and Attunu Passau (burning kemenyang) ceremonies. This form of sanction is a deterrent effect so that the community truly understands the importance of implementing the Pasang and use of forest areas.